2019
DOI: 10.1177/2473011419892240
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of First Tarsometatarsal Arthrodesis Constructs Over Prolonged Cyclic Testing

Abstract: Background: Traditionally, a lengthy period of nonweightbearing is required following arthrodesis of the first tarsometatarsal (TMT) joint in order to provide a stable healing environment for the bones. The goal of this research was to determine the resistance to plantar gapping of 2 locked intramedullary devices and a medial plate with crossing screw, all specifically designed for hallux valgus correction, and compare them to traditional 2-crossing screw fixation under a cyclic testing protocol. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Crossed screw configurations have traditionally been the method of fixation for primary arthrodesis of TMT joints [17,22,23]. A total of seven studies compared a variety of constructs against crossed screws across the first three TMT joints [17][18][19]22,23,27,29].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Crossed screw configurations have traditionally been the method of fixation for primary arthrodesis of TMT joints [17,22,23]. A total of seven studies compared a variety of constructs against crossed screws across the first three TMT joints [17][18][19]22,23,27,29].…”
Section: Discussionmentioning
confidence: 99%
“…Crossed screw configurations have traditionally been the method of fixation for primary arthrodesis of TMT joints [17,22,23]. A total of seven studies compared a variety of constructs against crossed screws across the first three TMT joints [17][18][19]22,23,27,29]. Of those seven studies, five found a significant advantage to alternative constructs compared to crossed screws, with the other two studies finding no significant difference between alternative methods and screw fixation at the first TMT joint [17][18][19]22,23,27,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations